Perception of Orthodontic Treatment Need Among Orthodontists, General Dentists and Lay People - Burcu Bayrak; Gülçin Doğusal; Melike Kan; Mine İdil Baltalı; Meryem Bayam; Ömür Polat-Özsoy; Bulem Yüzügüllü (Galenos Yayinevi, 2012)
Aim:The main objective of our study was to examine the possible differences in dental esthetic perceptions among dentists, orthodontists and laypeople.Subjects and Methods:The participants of the study consisted of 3 different groups as orthodontists, dentists who have at least 4 years clinical experience and laypeople. Thirty individuals were selected for each group. All the selected people were asked to complete the questionnaires. Assessment of treatment need was obtained by evaluating the Aesthetic Component (AC) of Index of Orthodontic Treatment Need (IOTN). This index contains a series of 10 black and white photographs of anterior teeth displaying varying degrees of malocclusion. The participants of this study were asked to rank each black and white photograph between 1 and 10 according to their perception of orthodontic treatment need.Results:There were only minor differences in perception of orthodontic treatment need. Differences were detected in photographs 1 and 9. In photograph 1, orthodontists and dentists gave similar scores but lay people scored higher than dental professionals.Conclusion:The present study aimed to investigate the possible differences in perception of orthodontic treatment need among orthodontists, general dentists and lay people and the results found only minor differences between the groups.